The Effect of Electromagnetic Radiation On Health And Measures To Prevent Its Negative Effects (Eurasian Research Bulletin, 2024)
The article is based on a system-dialectical, spatial, and integrated approach, in which the electromagnetic field's effects on the human body have been deeply and comprehensively explored. The main ways to protect against the electromagnetic field have been rationally defined, as well as preventive measures to reduce its negative impact.